Pengaruh Kepemilikan Manajerial, Komisaris Independen, Financial Distress terhadap Pengungkapan Sukarela - Asih Pratiwi; Mayar Afriyenti (Universitas Negeri Padang, 2023)
This study aims to examine the effect of Managerial Ownership, Independent Commissioner, Financial Distress on Voluntary Disclosure in manufacturing companies listed on the Indonesia Stock Exchange for the 2015-2019 period. This type of research is quantitative. The population used in this study is a manufacturing company listed on the Indonesia Stock Exchange (IDX) with a total sample of 170 samples using purposive sampling method. The analysis was performed using multiple linear regression models. The results of this study indicate that: (1) Managerial Ownership has a negative and insignificant effect on the structure of Voluntary Disclosure (2). Independent Commissioner has a negative and significant effect on Voluntary Disclosure (3) Financial Distress has a positive and significant effect on Voluntary Disclosure.